2017
DOI: 10.1149/2.0021710jes
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Stability of (Pr1-xNdx)2NiO4+δas Cathodes for Oxide Fuel Cells: Part VI. The Role of Cu Dopant on the Structure and Electrochemical Properties

Abstract: Phase instability in praseodymium nickelates is a major concern for the long-term operations of solid oxide fuel cells since it may lead to the performance degradation. In this work, praseodymium nickelates (ex. Pr 2 NiO 4+δ ) have been stabilized via substitution on both Pr-and Ni-sites. Systematic studies over a wide range of compositions were conducted via long-term thermal annealing studies (T ≤ 870 • C) and electrochemical tests in full cells. Proposed (Pr 0.50 Nd 0.50 ) 2 Ni 1-y Cu y O 4+δ compositions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Ea,LNO=1.3 eV vs. Ea,NNO=1.15 eV) [50]. The purity of the nickelate phase in ceramic electrodes can be closely correlated to the cell performance (the higher the phase purity the higher the performance) [48][49][50][51]. We surmise the sintering temperature is too low for PNO, but to avoid oxidation, it is limited to <900 °C.…”
Section: Nickelatesmentioning
confidence: 91%
“…Ea,LNO=1.3 eV vs. Ea,NNO=1.15 eV) [50]. The purity of the nickelate phase in ceramic electrodes can be closely correlated to the cell performance (the higher the phase purity the higher the performance) [48][49][50][51]. We surmise the sintering temperature is too low for PNO, but to avoid oxidation, it is limited to <900 °C.…”
Section: Nickelatesmentioning
confidence: 91%
“…Initial studies of the Pr 2 NiO 4+δ and Nd 2 NiO 4+δ phases produced electrode performances with slightly higher ASRs; Ferchaud et al reported an ASR of 2.5 Ω cm 2 for PNO at 600 • C [22]. A 50:50 composition, PrNdNiO 4+δ (PNNO), reported by Dogdibegovic et al, presented an ASR of 0.7 Ω cm 2 at 800 • C [23]. A recent attempt at improving the performance of these materials by Bassat et al yielded the remarkable performance of 0.03 Ω cm 2 at 700 • C for a PNO cathode [24].…”
Section: Introductionmentioning
confidence: 99%
“…The structural refinement on PNNO-Cu y series, reported in our previous work, showed an increase in the cell volume with increasing molar fraction of Cu, mainly driven by a 0.90% increase in the c lattice parameter. In addition, the fractional position coordinates on heavy metal cations (Pr, Nd) indicated an elongation in the z direction and overall compression in the y direction, while the orthorhombic Bmab symmetry was retained.…”
Section: Resultsmentioning
confidence: 99%
“…Supercells containing 56 atoms were constructed, and the self-consistent electronic structure calculations were performed for Pr 2 NiO 4 , Pr 2 Ni 0.875 Cu 0.125 O 4 , PrNdNiO 4 , and PrNdNi 0.875 Cu 0.125 O 4 cathode materials. The calculations were carried out using the density-functional theory (DFT) method as implemented in the Vienna ab initio simulation package VASP . Projector augmented wave (PAW) pseudopotentials were used .…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation